ENT 530 Principles of Entrepreneurship: Arts of Interior Design / Shahrul Nizam Saiful Bahari - Saiful Bahari, Shahrul Nizam (2021)
Arts of Interior Design has the objective to maximize the satisfaction of our customers based on their own preferences. Futhermore, our product asthetics and quality will surely be taking in accord. Our business has started on 16 November 2020 and we have decided to custom a decorative products hand made with a few engrave wood for home decorations. We also selling a few type of homes decoratives which is hydroponic wall decoration with wood font and a few type of home decoratives light. Based on our customer review, our product have a high quality with affordable prices. Our target market is to the users that passionate in home decorations and interior designing. We are focusing to promoting in Facebook pages and in market place in thru facebook. We also focusing on rural area more to the city. Ever since our early business opening days, we manage to sell about 5 sets of hydroponic decoratives and 5 pieces of decoratives light. Promoting widely helps us resulting having more customers and orders at a time. Surely, our friendly-concept plays the major rule in gaining customer much quicker. Therefore, our business will grew much faster than we imagine.